2019
DOI: 10.1089/vbz.2018.2354
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Human Cystic Echinococcosis in Latvia

Abstract: Despite the importance of Echinococcus spp. in the Baltic States, little is known about the locally relevant risk factors for contracting the human disease they can cause. The aim of this study was to compare the frequency of selected potential risk factors in individuals diagnosed with cystic echinococcosis (CE) in 1999-2015 and matched controls. The diagnoses of the cases were based on combination of serology and diagnostic imaging, and they were not confirmed to species level of the causative parasite. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In China, there are a large number of pet dogs and stray dogs, and a previous meta-analysis found that the combined prevalence of E. multilocularis and E. granulosus in dogs was 7.3% ( 57 ). Furthermore, because dogs belonging to rural families are less likely to obtain nutritious food, their diets are supplemented by hunting small mammals, which are intermediate hosts of E. multilocularis ( 58 ), or by being fed livestock viscera, which supports the lifecycle of E. granulosus ( 59 ). The large number of infected dogs and close contact with dogs are the causes of the high rates of E. multilocularis and E. granulosus in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In China, there are a large number of pet dogs and stray dogs, and a previous meta-analysis found that the combined prevalence of E. multilocularis and E. granulosus in dogs was 7.3% ( 57 ). Furthermore, because dogs belonging to rural families are less likely to obtain nutritious food, their diets are supplemented by hunting small mammals, which are intermediate hosts of E. multilocularis ( 58 ), or by being fed livestock viscera, which supports the lifecycle of E. granulosus ( 59 ). The large number of infected dogs and close contact with dogs are the causes of the high rates of E. multilocularis and E. granulosus in humans.…”
Section: Discussionmentioning
confidence: 99%
“…This will increase the risk of echinococcosis. On the other hand, many dog owners fed dogs the viscera of livestock, which supports the lifecycle of echinococcus [52]. Dogs, the main participants in transmission, play a key role in prevention and control.…”
Section: Discussionmentioning
confidence: 99%